Morpho-orthographic preferences among typical and poor native Arab readers. Issue 2 (3rd July 2019) - Taha, Haitham; Taha, Hanada
ABSTRACT: The current study examined how morpho-orthographic knowledge affects the orthographic preferences among typical and poor native Arab readers. Two-hundred participants (100 typical and 100 poor readers) from second to sixth grade were tested using pseudo-orthographic choice task, which was composed from fifty pairs of homophonic pseudowords. For each pair of homophonic pseudowords, the participants were asked to circle the one that appears acceptable as real word according to its written orthographic pattern. The results revealed that the accuracy levels among typical readers were significantly higher than those of poor readers. Among the typical group of readers, older participants showed higher accuracy levels than younger readers, while this pattern of performance was not shown among the poor readers, indicating that morpho-orthographic knowledge which affect the spelling and orthographic preferences in Arabic is a result of intact reading development.